Meningkatkan Literasi Bahasa Inggris Anak-Anak Panti Asuhan Budi Mulia Melalui Buku Bilingual di Era Globalisasi - Zahra, Rani; Arisman; Minallah, Fadlan; Insani, Nur (JURNAL MASYARAKAT NEGERI ROKANIA, 2024)
The aim of this PkM activity is to explain to children from orphanages about the importance of improving English literacy in this era of globalization. Improving English literacy is the most important key in facing global challenges in this information era. With the development of technology and globalization, the ability to communicate in English is not just an additional skill, but has become an urgent need. Therefore, English language proficiency education is an important foundation for individuals to acquire the skills needed in various life situations.English has a very important role in improving literacy. In this case, we chose the target participants as children from Budi Mulia’s orphanage, so that awareness of the importance of literacy and mastery of foreign languages is embedded from an early age which will be useful in the future.